Covid-19 Challenges and the Role of Islamic Fintech: A Literature Review - Afrizal (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to conduct a review of Islamic Fintech research development from 2020 to 2022 related to the Coronavirus Disease 2019 (COVID-19) and the role of Islamic fintech. This research is a qualitative-descriptive study utilizing a literature review approach. The literature review was conducted by collecting journal articles relevant to the research objectives using the Publish or Perish (PoP) application, followed by content analysis using the Scopus database. The content analysis identifies two related streams concerning Covid-19 challenges and the role of Islamic Fintech. In detail, Islamic fintech and distributed ledger technology (Blockchain, 1 article) and financial inclusion (6 articles). By conducting a content analysis on each stream, we reveal that the cointegration of Fintech in Islamic finance has enormous potential in elevating socio-economic development, particularly for the underdeveloped community, unbanked people, and micro-small enterprises (MSEs) In addition, the adoption of fintech in Islamic finance will support the government in improving financial inclusion, conquering financial crises, such as COVID-19's crisis